1993
DOI: 10.1111/j.1468-3148.1993.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Comparisons, Stigma and Mainstreaming: The Self Esteem of Young Adults With a Mild Mental Handicap

Abstract: As people with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 17 publications
1
47
1
1
Order By: Relevance
“…There is evidence that for people with disabilities stigmatization can have a negative impact on their psychological well-being, lowering their self-esteem and negatively affecting their mood (Abraham et al 2002;Dagnan and Waring 2004;Szivos-Bach 1993). Those who were most aware of being stigmatized had the lowest self-esteem scores (Szivos 1991).…”
Section: Self-esteemmentioning
confidence: 99%
“…There is evidence that for people with disabilities stigmatization can have a negative impact on their psychological well-being, lowering their self-esteem and negatively affecting their mood (Abraham et al 2002;Dagnan and Waring 2004;Szivos-Bach 1993). Those who were most aware of being stigmatized had the lowest self-esteem scores (Szivos 1991).…”
Section: Self-esteemmentioning
confidence: 99%
“…However, there is evidence that different educational settings may expose individuals to different levels of stigmatised treatment (Cooney et al, 2006). A study conducted by Szivos-Bach (1993) found that young people with ID who are educated in integrated schooling often believe that their social identity is devalued. Those educated in segregated settings may be protected from an insight into the devalued status that people with ID can hold in society (Todd, 2000).…”
Section: Educational Opportunities For Students With Idmentioning
confidence: 99%
“…Szivos‐Bach () found that those who had the greatest awareness of stigma and subsequent lowest self‐esteem reported the highest levels of feeling inferior (i.e., feeling fundamentally different to others), and the lowest self‐concept/self‐efficacy (i.e., feeling the least likely to live up to their ideals and aspirations). This was supported by Dagnan and Waring (), who found that perceived stigma was strongly significantly correlated ( r = .41, p < .05) with perceived other‐to‐self‐negative evaluations (i.e., external shame).…”
Section: Resultsmentioning
confidence: 99%
“…However, it remains open to debate as to whether this is a solely positively adaptive process in maintaining/sustaining one's self‐esteem, or in some instances as a form defence against shame through denial (Allan & Gilbert, ; Sinason, ). There is evidence that both upward or downward social comparisons can reduce prosocial behaviour towards and empathy for others (Yip & Kelly, ), lead to behavioural avoidance of others and social distancing (Chen & Shu, ), and to other forms of less prosocial behaviour such as derogating against similar others as a way of maintaining one's self‐esteem (Szivos‐Bach, ). Only one study in this review reported evidence relating to this more externalizing, humiliating response to feeling shamed in individuals with intellectual disabilities (Szivos‐Bach, ).…”
Section: Discussionmentioning
confidence: 99%